Hodnocení průmyslového dědictví - Navrátil, Oldřich (Vysoké učení technické v Brně. Fakulta architektury)
Hlavním tématem je zhodnocení účinnosti současné péče ( nejen památkové) , ochrany a záchrany průmyslového dědictví. Poukázání na kritické problémy spojené s ukončením výroby tradičních odvětví, které sehrály významnou roli v historii měst. Nyní opuštěné budovy a uvolněné areály jsou reprezentanty paměti místa nebo jeho prosperity. Noví majitelé nesdílejí kladný postoj k průmyslovému dědictví, developeři hledají nové pozemky, města a jeho obyvatelé mají nové potřeby. Výsledek práce bude sloužit k orientaci, jaké jsou přístupy v evropských zemích a doporučení monitoringu průmyslového dědictví a jeho hodnocení k zamezení nenávratných škod.

The main subject is evaluation of effective use in terms of care (not only within protection of monuments) in order to save and protect industrial heritage. Pointing out on critical issues connected with the end of production of traditional branches which played the key role in historical development of our cities. Nowadays abandoned buildings and sites are represented by memory of the place or its prosperity. New owners often don't share the positive approach to the industrial heritage, developers are seeking new sites, cities and inhabitants have developed new needs through the time. The work will demonstrate examples within European context and will make recommendations in monitoring and classification of industrial heritage to prevent undo able losses.
Evaluation of industrial heritage
Keywords: Obnova; revitalizace; konverze; recyklace; konzervace; demolice; kulturní památka; průmyslová archeologie; kritéria hodnocení; klasifikace; záchrana; ochrana; památková péče; aktéři záchrany; kontext; brownfield; průmyslové dědictví; identita místa; udržitelný rozvoj.; Renewal; revitalisation; conversion; recyclation; conservation; demolition; cultural heritage; industrial archeology; criteria of evaluation; classification; rescue; protection; monument protection; stakeholders; context; brownfield; industrial heritage; place identity; sustainable development.